Lentiviral vectors titration using real-time PCR - Allahverdi, Amir; Eskandari, Fatemeh; Moghadasi, Mohammad Hossein; Azad, Mehdi; Goudarzi, Mehdi; Abroun, Saied; Soleimani, Masoud (Archives of Advances in Biosciences, 2015)
Lentiviral vectors (LVs) are useful vehicle for genetransfer to dividing and non-dividing cells and genetic manipulations. However, the use of lentiviruses in studies requires an accurate titration technique.Quantitative real-time PCR (qPCR) is a sensitive technique for the indication and quantitation of retrovirals particles. In this study, we used the qPCR for lentiviral vector titeration. The puromycin resistance gene as templates for an SYBR green-based real-time qPCR method and detect lentiviral copy number integrated lentiviral DNA. Consequently, this studyshowed that theusing ofantibioticresistance genesviral particles titration maybeefficient with highly accuracy.